A systematic review of the frequency of features of the seven‐point checklist in proven cutaneous melanoma: The importance of change - Nicola M. Congdon; Christina M. Davis (Wiley, 2023)
Abstract Background Pigmented skin lesions in human adults can present with several different visible features that may indicate signs of malignancy, particularly melanoma. Patient and clinician awareness of these features can aid the early recognition and melanoma diagnosis improving patient outcomes. The seven‐point checklist (7PCL) is a clinical prediction rule advocated by the National Institute for Health Care Excellence to aid the assessment of pigmented skin lesions in primary care to indicate referral for specialist opinion. Objectives Assess the current evidence to establish which features of the 7PC present more frequently, so public education and clinician assessment can be focused to maximise early diagnosis and minimise referrals of benign lesions. Methods A systematic review of published evidence identified studies that assessed the seven features of the 7PCL in histologically proven melanomas. Two independent reviewers screened eligible studies and independently extracted data and assessed quality. Results 112 studies were screened, 20 were assessed in full, seven met the inclusion criteria. 1184 histologically diagnosed melanomas were assessed using the 7PCL. Four studies involved patients assessing 335 melanomas, and three involved clinicians who assessed 849 melanomas. The most common feature identified was a change in size of the lesion, and the least common was inflammation. Conclusions The most frequently occurring features of melanoma involve shape, size and colour, however focussing on changes in features, rather than irregularity, is more likely to identify early melanoma and increase the accuracy of referrals.